A helyi termékek jelentősége a vidékgazdaságban - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
As we experienced now adays, the accelrating changes of the unpredictable profitability of the economy, the changing agrar policy, the problems caused by the intensive agriculture and the climate change are threatening the viability and the health of the natural enviroment and the population. These changes can not be left ignored. The aim of my thesis, to demonstrate, one of the effective instruments of the reduction of vulnerability is the creation and maintenance of diverse local economy. 1 point tot the local products and the local consum ption can be the sustaninig force of the rural population, and to those opportunities which enable a more liveable enviroment.